A combined fuzzy MCDM approach for selecting shopping center site: An example from Istanbul, Turkey - Onut, Semih; Efendigil, Tugba; Kara, Selin Soner (PERGAMON-ELSEVIER SCIENCE LTD, 2010)
The aim of this study is to model shopping center site selection problem for a real world application in Istanbul which is the most populated city in Turkey. Since Turkish metropolitan cities have been attracting a large population from smaller cities and rural areas, it has caused a considerable increase in the population of the big cities of Turkey. The growth in population and the enormous shift of people from old to newly developed districts in Istanbul also create new spending demand areas. This is the most powerful motivation to generate new sites in the city for locating attractive shopping centers. A number of conflicting qualitative and quantitative criteria exist for evaluating alternative sites. Qualitative criteria are often accompanied by ambiguities and vagueness. This makes fuzzy logic a more natural approach to this kind of multi criteria decision making (MCDM) problems. The paper proposes a combined MCDM methodology. Fuzzy AHP (analytic hierarchy process) is utilized for assigning weights of the criteria for site selection and fuzzy TOPSIS (technique for order preference by similarity to ideal solution) is used to determine the most suitable alternative using these criteria weights. The study was followed by the sensitivity analysis of the results. (C) 2009 Published by Elsevier Ltd.
Keywords: Shopping center; Site selection; Fuzzy TORSIS; Fuzzy AHP; GROUP DECISION-MAKING; LOCATION; SYSTEM; MALL; AHP; Computer Science; Engineering; Operations Research & Management Science